2012
DOI: 10.1111/j.1708-8208.2009.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Treatment of Peri‐Implantitis Bone Defects with a Combination of Autologous Bone and a Demineralized Xenogenic Bone Graft: A Series of 36 Defects

Abstract: Within the limits of the study, we conclude that for bone defects larger than 4 mm in case of peri-implantitis, this single surgical intervention provided a reliable method to reduce bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 28 publications
(59 reference statements)
7
113
0
3
Order By: Relevance
“…The methods to decontaminate implant surfaces, including the use of air abrasives and the use of biological agents (enamel matrix derivatives and platelet-derived growth factors) in combination with bone grafts (Froum et al, 2012), might be associated with higher bone fill. The use of "xenograft derived bone substitutes with autografts" (Wiltfang et al, 2012) yielded an aboveaverage defect fill. Defect features (Schwarz et al, 2010), implant surfaces (Roccuzzo et al, 2011), and grafting materials (Aghazadeh et al, 2012) are also factors that may explain the variability in defect fill among the included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods to decontaminate implant surfaces, including the use of air abrasives and the use of biological agents (enamel matrix derivatives and platelet-derived growth factors) in combination with bone grafts (Froum et al, 2012), might be associated with higher bone fill. The use of "xenograft derived bone substitutes with autografts" (Wiltfang et al, 2012) yielded an aboveaverage defect fill. Defect features (Schwarz et al, 2010), implant surfaces (Roccuzzo et al, 2011), and grafting materials (Aghazadeh et al, 2012) are also factors that may explain the variability in defect fill among the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…The points that were used included the implant platform (Khoury and Buchmann, 2001;Deppe et al, 2007;Roccuzzo et al, 2011;Aghazadeh et al, 2012;Froum et al, 2012;Wohlfahrt et al, 2012), the first thread (Roos-Jansaker et al, 2007a, 2007b, and the bone crest (Schwarz et al, 2009;Schwarz et al, 2010;Schwarz et al, 2012;Wiltfang et al, 2012). It might be preferable to describe both the supracrestal and the subcrestal components of bony defects so that the changes of the crestal location in relation to the implant platform and the amount of defect fill at the bottom of the defects can be readily evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In eigenen Untersuchungen konnte nach Dekontamination der Implantatoberfläche mit Phosphorsäure und Auffüllung der periimplantären ossären Defekte mit autologem Knochen und demineralisiertem xenogenem Knochenersatzmaterial (Collos E/Ossacur, Oberstenfeld) im Verhältnis 1:1 mit dieser Behandlung ein Erfolg bezüglich des Knochenverlusts bei Knochenläsionen >4 mm, die durch eine Periimplantitis bedingt waren, gezeigt werden [39]. Diese ergänzende Behandlungsmethode weist noch nach mehreren Jahren Nachbeobachtung gute Ergebnisse bezüglich der periimplantären Sondierungstiefe und der radiologischen Kontrolle der Knochenhöhe auf ( [40], .…”
Section: Es Konnte Keine üBerlegenheit Eines Bestimmten Reinigungsverunclassified
“…28 Sahrmann et al 2011 in a systematic review have concluded that complete fill of the bony defect using GBR seems not to be a predictable outcome 29 Well-controlled trials are needed to determine predictable treatment protocols for the successful regenerative treatment of peri-implantitis using GBR technique.…”
Section: Surgical Treatment Of Perimentioning
confidence: 99%